(untitled) (Global Journal of Human-Social Science, 2023)
It all started with a toy bird a swallow helidon that the children in the villages around Asenovgrad town use to celebrate the coming spring and Baba Marta Grandma March a symbolic figure believed to mark the end of the winter The popularity of the swallow toy rivals that of t he traditional martenitsa red and white threads weaved in different shapes in this region At that time my focus of interest as a lecturer in toy design was on the history of toys and games The morphological analysis of the toy takes into consideration the profound symbolism and the allegorical nature of all the elements rooted in its formation As if its structure although not complicated at all contains all the fundamental symbols the rainbow-shaped element representing the sky and the celestial rainbow that sweeps over us like a magic semicircle bridge the horizontal element fundamental and supporting the whole construction and ends as a handle representing the earth as a symbol of stability the vertical placed axis reminding us of the World Cosmic Tree Axis mundi representing the connection between the higher spiritual heaven realm and the lower earthly material substance